Introduction to Gel Electrophoresis Lab - Virtual Simulation in Biotechnology Course - Ria Ria; Solihin Solihin; Septiandita Mailayfaiza; Najwa Syafkitamsana; Lia Junita Harahap (Bioedunis Journal, 2025)
Gel electrophoresis is a fundamental technique in molecular biology used to separate DNA fragments by size. However, limitations in laboratory facilities often hinder its implementation. This study aims to analyze students’ understanding of the operating principles of gel electrophoresis, the functions of its main components, and their ability to interpret DNA separation results through a virtual practicum on the LabXchange platform. The study employed a descriptive qualitative approach with 63 fifth-semester students from the Biology Education Program. Data were collected through observations during the simulation, analysis of DNA band patterns generated by the virtual experiment, and students’ responses in the worksheet. The findings indicate that the virtual simulation effectively visualizes the DNA migration process, enabling students to understand the roles of agarose gel, buffer, and electrical current in fragment separation. Students identified the relationship between fragment size and migration distance and evaluated the expected results based on electrophoresis theory. Thus, the virtual laboratory practicum proved to be an effective alternative learning method for enhancing conceptual understanding and analytical skills in gel electrophoresis.